Transformasi Sungai Musi: Antara Jalur Maritim dan Krisis Ekologi dalam Kehidupan Masyarakat Pesisir - Khoirunisa Az Zahra; Farida R Wargadalem; M Taofik Kurohman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The Musi River is the longest river in Sumatra Island with historical significance as a maritime trade route from the Sriwijaya Kingdom era to contemporary times. This research analyzes the transformation of the Musi River's function from a historical-ecological perspective and its impact on coastal communities. The study employs a qualitative approach with historical-descriptive methods through literature studies, field observations, and in-depth interviews. The findings indicate that the Musi River has experienced significant ecological degradation due to industrial pollution and domestic waste. Water quality parameters such as BOD, COD, and heavy metals exceed environmental standards. This transformation has caused economic degradation through declining fishery productivity, changes in fishermen's livelihoods, and loss of traditional maritime trade functions. Coastal communities face economic pressure, health problems, and limited access to clean water. Sustainable management of the Musi River encounters complex challenges including weak environmental law enforcement, limited waste treatment infrastructure, and low community participation. An ecosystem-based management approach integrating ecological, economic, and socio-cultural aspects through multi-stakeholder collaboration is required for the revitalization of the Musi River.